The role of technology in the water–energy–food nexus. A case study: Kerinthos, North Euboea, Greece - Sargentis, G.-Fivos; Mamassis, Nikos; Kitsou, Olga; Koutsoyiannis, Demetris (Frontiers in Water, 2024)
The Water-Energy-Food (WEF) nexus is a basic element of prosperity, yet it is not equally distributed in land. Human progress has optimized the function of WEF nexus to bridge the inequality gap. In order to study this progress, this study compares the preindustrial and modern agricultural practices in a Greek area. Interviews were conducted with an elderly man who lived in the 1950s, and the process was quantified in units of WEF. The same procedure was also carried out with modern farmers for modern practices. In comparing past and present agricultural processes, it's observed that today, a farmer can feed around 100 times more people. This feat has been achieved as modern practices push the land with energy sources by multiple ways (fuels, fertilizers). However, energy indices as energy ratio, net energy gain, specific energy, and energy productivity do not seem to be improved. Furthermore, farmers prefer to pump underground water for irrigation instead of utilizing the nearby river, as was done in the past when the river provided both energy to the watermill and abundance of water for irrigation. In addition, as wheat's price is depending on stock market, even if in 2023 there are risks of food security, the cultivation of wheat was not economically efficient for famers in this area in 2023.